Coiling Versus Stenting for Giant Cavernous Sinus Aneurysms: A Case Report on the Resolution of Oculomotor Nerve Palsy - Nelsi Marintan Tampubolon; Geizar Arsika Ramadhana (HM Publisher, 2025)
Giant intracranial aneurysms (GIAs), defined as those exceeding 25 mm, represent a subset of cerebrovascular lesions with significant potential for morbidity due to mass effect and rupture. Compression of cranial nerves, particularly the oculomotor nerve (N. III), by these aneurysms can lead to debilitating symptoms such as ptosis, ophthalmoplegia, and diplopia. Endovascular management, including coiling and stenting, offers minimally invasive treatment options, but the optimal approach remains a subject of ongoing investigation. We present a case of a 28-year-old male with a giant aneurysm of the right cavernous sinus who presented with progressive right oculomotor nerve palsy, characterized by marked ptosis and visual impairment. Initially scheduled for stent placement, the patient underwent endovascular coiling following diagnostic digital subtraction angiography (DSA). Serial neurological assessments and follow-up DSA evaluations were conducted to monitor treatment efficacy and aneurysm stability. In conclusion, this case demonstrates that endovascular coiling can be a valuable therapeutic strategy for giant cavernous sinus aneurysms manifesting with oculomotor nerve compression. Despite the theoretical advantages of stenting in promoting aneurysm obliteration and reducing mass effect, coiling facilitated significant and sustained clinical improvement, specifically the resolution of ptosis and amelioration of visual deficits in this patient. This case underscores the importance of individualized treatment planning in the management of complex intracranial aneurysms.